The Effect of Intervention on Semi Fowler and Fowler Positions on Increasing Oxygen Saturation in Heart Failure Patients - Nandar Wirawan; Nandi Periadi; M Iqbal Kusuma (Jurnal KESANS : Kesehatan dan Sains, 2022)
Introduction: In Indonesia, data from the 2013 Basic Health Study showed the prevalence of heart failure was 0.3%, an estimated 530,068 people based on a doctor's diagnosis. Cardiovascular disease is a disease that interferes with the function of the heart and blood vessels, clinical symptoms in patients with congestive heart failure (CHF) include dyspnea, orthopnea, dyspnea and paroxysmal nocturnal dyspnea (PND), pulmonary edema, ascites, pitting edema, weight gain and even shock. cardiogenic. Method: The method used in this research is an experimental research method. The type of research used is quasi-experimental (quasi-experimental). Objective: The purpose of this study was to determine the effect of semi-Fowler and Fowler positions on increasing oxygen saturation in heart failure patients at Sumedang Hospital. Results and Discussion: The first output shows the difference in oxygen saturation of the rear half-fowler of 45 and 90, on the rear half-fowler an average of 94.25, the minimum and maximum values ??of 90-97, Then to catch the rear bird of 90 the average is 96.50 and min and max are 93-99. Conclusion: The effect of half fowler and fowler positions given by Sumedang Hospital to increase blood oxygen saturation in heart failure patients with a value of 90.50. For the second half of Fowler's 45?, get the values, min 90 and max 97 and mean 94.25.